Інновації як основа стійкого розвитку сільськогосподарських підприємств - Качула, Світлана Валентинівна; Kachula, Svitlana; Дудка, С. В.; Dudka, S. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2024)
В статті здійснено ґрунтовний аналіз теоретичних і практичних аспектів сучасних тенденцій у сфері інноваційних технологій сільськогосподарських підприємств. Проаналізовано основні фактори, що визначають темпи впровадження інновацій, розкрито ключові механізми, які забезпечують інтеграцію новітніх технологій у виробничі процеси. Досліджено головні виклики, які постають перед сільськогосподарськими підприємствами в умовах технологічної трансформації (адаптація до швидких змін, необхідність нарощування інвестицій у наукові дослідження,підтримка інноваційної інфраструктури, забезпечення підготовки кваліфікованих кадрів, здатних ефективно працювати в нових технологічних умовах). Надано всебічний огляд основних інноваційних тенденцій, які мають вирішальне значення для довгострокового економічного зростання та забезпечення глобальної конкурентоспроможності. Підкреслена необхідність активізації співпраці між різними секторами економіки та ефективного використання науково-технологічного потенціалу для забезпечення стабільного інноваційного розвитку в мінливому глобальному середовищі. The article examines the main aspects of the development of modern innovative technologies in the context of global digitalization and economic transformation. Key drivers influencing the adoption of innovations across various economic sectors, including agriculture, are analyzed. These include technological progress, regulatory policies, investment, shifts in consumer behavior, and workforce training levels. The nature and specifics of innovation application in agricultural enterprises are explored. It has been established that modern innovations, including artificial intelligence, block chain, automation, and 3D printing, offer significant opportunities to enhance productivity, optimize production processes, and develop innovative products and services in the agricultural sector. Special attention is given to analyzing the role of state policies and institutional support as primary catalysts of innovation activity, as well as the influence of the private sector on innovation processes. In this context, the article analyzes factors that foster cooperation among government organizations, businesses, and research institutions, which collectively create conditions for effective innovation ecosystems. The greatest challenges in the contemporary innovation environment are identified, including the rapid pace of technological change, the need for investment in scientific research, adaptation to global trends, and ensuring high quality workforce training to meet new demands. It has been determined that the successful integration of innovations into the socio-economic domain is feasible only through the collaboration of all participants in the innovation process, supported by effective planning, robust infrastructure, and political backing. Innovations in the agricultural sector are emphasized as not only a means of increasing production efficiency but also a crucial tool for improving rural living standards, mitigating environmental risks, and enhancing the agricultural economy's resilience to global challenges. As a result of the study, an in-depth analysis of innovation processes has been conducted, the primary challenges faced by modern countries in technology implementation have been identified, and the need for effective cross sect oral collaboration to ensure the successful development of innovation potential has been outlined.
Innovation as the basis for sustainable development of agricultural enterprises
Keywords: інновації; innovations; інноваційний розвиток; innovative development; сталий розвиток; sustainable development; сільськогосподарські підприємства; agricultural enterprises; аграрні інновації; agricultural innovation; інноваційна стратегія; innovation strategy